STUDENTS’PERCEPTIONS ON THE USE OF WHATSAPP IN WRITING ACTIVITIES: A CASE STUDY AT SMPN 1 PAGAR GUNUNG (English Community Journal, 2022)
The aim of this study was conducted to find out the students’ perceptions on the use of WhatsApp in writing activities at SMPN 1 Pagar Gunung. This study used a qualitative research design. The participants of this study were the eleventh grade students of SMPNegeri 1 Pagar Gunung which consisted of six students by usingpurposive sampling with maximum variation sampling. The data were collected by using semi-structured interview through open ended questions. The data were analyzed by using thematic analysis technique. The findings of this study revealed that there were advantages and disadvantages on the use of WhatsApp in writing activities, as follows: (a) perceived progress of vocabulary, (b) independent from time and location, (c) internet connection problem, (d) costly to use, and (e) no grammatical improvement. Then, by knowing the students’ perceptions on the use of WhatsApp in writing activities, the students can explore by themselves on the use of e-learning to upgrade the English proficiency.